2015
DOI: 10.4103/1008-682x.138186
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of membrane occupation and recognition nexus repeat containing 3, meiosis expressed gene 1 binding partner, in mouse male germ cells

Abstract: Mammalian spermatogenesis is a well-organized process of cell development and differentiation. Meiosis expressed gene 1 (MEIG1) plays an essential role in the regulation of spermiogenesis. To explore potential mechanisms of MEIG1's action, a yeast two-hybrid screen was conducted, and several potential binding partners were identified; one of them was membrane occupation and recognition nexus repeat containing 3 (MORN3). MORN3 mRNA is only abundant in mouse testis. In the testis, Morn3 mRNA is highly expressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…Function of the gene product, membrane occupation and recognition nexus repeat containing 3 (MORN3), has not been functionally characterized. However in mice, from its specific expression in testis and its property of binding to meiosis expressed gene 1 (Meg1), a regulator of spermatogenesis, it has been suggested that Morn3 also plays a role in sperm formation [ 44 ]. Based on this suspected biology, currently there is little evidence to consider MORN3 as a candidate gene in KD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Function of the gene product, membrane occupation and recognition nexus repeat containing 3 (MORN3), has not been functionally characterized. However in mice, from its specific expression in testis and its property of binding to meiosis expressed gene 1 (Meg1), a regulator of spermatogenesis, it has been suggested that Morn3 also plays a role in sperm formation [ 44 ]. Based on this suspected biology, currently there is little evidence to consider MORN3 as a candidate gene in KD susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Besides PACRG and SPAG16L, MEIG1 also associates with transcription factor-like 5 protein (TCFL5) ( Shi et al, 2013 ), and membrane occupation and recognition nexus repeat-containing 3 (MORN3) (Zhang et al, 2014). Interestingly, both TCFL5 and MORN3 are present in the manchette, and MORN3 localization is dependent on MEIG1 ( Zhang et al, 2014 ). These proteins may modulate MEIG1/PACRG function.…”
Section: Discussionmentioning
confidence: 99%
“…61 MORN3, expressed in the manchette of the elongating spermatid, was recently identified as another MEIG1-interacting protein. 62 …”
Section: Manchette Of Elongating Spermatidsmentioning
confidence: 99%